French Language Analysis in Drama : The Romancers and Implications for SLA - Novinda, Kushardiyanti; Daud, Jiwandono; Khairiyah Eka, Januaristi (Lingua Litteria Journal, 2025)
This study examines the French language usage in the drama The Romancers and its relevance for Second Language Acquisition. The study focused on the drama text, which contains a number of French phrases, for English teaching sophomores. This study analyzes The Romancers through French descriptive analysis, paying attention to the French Sociolinguistics corpus, cultural elements, and thematic concerns that give texture to French in the play. Using qualitative approaches, this research studies important conversations and relationships of the characters, concentrating on French idioms, slang, and other formal and decorative forms of language characteristic of French. This study offers new insights into how texts from SLA offer rich resources for SLA through real language practices within culture and context for increased proficiency in SLA. Through the integration of literary study bolstered by effective approaches to language teaching, this study elevates the importance of teaching English through literary texts. Scaffolded instruction provides rich resources through which learners can appreciate the language and the culture, resulting in increased motivation towards understanding the language, leading to a strengthened SLA process. This study adds important perspectives to the discussion of how literature can provide scholarly texts in the context of teaching.